Nematode community structure in potato fields of Kurdistan province, western Iran - Reza Ghaderi; Habiballah Hamzezarghani (Journal of Crop Protection, 2021)
Potato is one of the most important crops produced in Kurdistan province, western Iran. Although several species of plant-parasitic nematodes have been reported in association with these potato fields, no comprehensive nematode community structure has been investigated. The present study reports the frequency, abundance and prominence value of all nematode groups from 40 potato fields across Ghurveh and Dehgolan regions. Bacterivorous nematodes showed the highest frequency, abundance and predominance in the region, followed by herbivorous (plant-parasitic nematodes), fungivorous and omnivorous nematodes. Predatory nematodes (carnivores) were not recovered probably because field soils were highly disturbed. Root-lesion nematodes were the most predominant among the identified plant-parasitic nematodes. The calculation of the indices of ecosystem function, as well as the plotting colonizer-persister (c-p) triangle, food web faunal analysis and metabolic footprint of the potato fields revealed that most of the studied fields had high proportions of c-p1 and c-p2 nematodes, but nematode individuals of c-p3-5 counted fewer in the population. According to the present study, 50% of the sampled fields represent either stressed and enriched, 30% could be considered as stable and enriched, and 20% may be described as stressed and depleted in terms of their soil nematode food webs. The current study provides the first known study in Iran on nematode assemblages and their implication in soil health.